Evaluasi Usability Sistem Instalasi Access Point Menggunakan Metode System Usability Scale - Sudarmin Sudarmin; Ahlis Noor Kholili (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
The rapid development of networking technology and the increasing demand for skilled professionals in the information technology sector require vocational high school (SMK) graduates to possess not only technical competencies but also entrepreneurial and financial management skills. This study aims to analyze the usability of an Access Point installation system and examine its potential to support learning in operational cost efficiency and profit margin calculation for network installation service businesses. A quantitative approach was employed using the System Usability Scale (SUS) as the evaluation method. The study involved 26 vocational high school students who had completed an Access Point installation practicum. Data were collected through the SUS questionnaire and observations during the practical learning process. The results showed that the system achieved a SUS score of 77.5, which falls into the Good category with an Acceptable level of usability. These findings indicate that the system is easy to use and effectively supports the learning process of Access Point installation. In addition to enhancing students' technical competencies, the system also facilitates their understanding of operational cost efficiency, service pricing, and profit margin calculation as essential entrepreneurial skills. This study demonstrates that integrating usability evaluation, computer networking education, and entrepreneurship provides a relevant approach to improving vocational students' readiness for both employment and self-employment.